Framings of Food Waste: How Food System Stakeholders Are Responsibilized in Public Policy Debate. Issue 2 (April 2022) - Mesiranta, Nina; Närvänen, Elina; Mattila, Malla
Food waste is a global sustainability issue that demands that multiple stakeholders participate in solving it. This article examines how different food system stakeholders are held responsible in the policy debate related to food waste reduction. The study adopts a framing approach, paying attention to the construction and negotiation of what is going on in the food waste–related public policy debate. The data consist of documents generated as a result of food policy development processes in Finland. The authors identify four framings—eco-efficiency, solidarity, safety, and appreciation—within which the issue of food waste is presented differently and different stakeholders responsibilized. The framings reveal the nature of food waste as a boundary object, a flexible and open-ended object that has different context-dependent meanings. The study extends marketing literature on responsibilization by investigating several stakeholders beyond consumers. Additionally, considering food waste a boundary object sheds light on how stakeholders, even those with conflicting interests, can debate policy measures collaboratively. Finally, the authors outline policy implications related to each framing.